2016
DOI: 10.1021/acs.est.6b02253
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid Pesticides as Endocrine Disruptors: Molecular Mechanisms in Vertebrates with a Focus on Fishes

Abstract: Pyrethroids are now the fourth most used group of insecticides worldwide. Employed in agriculture and in urban areas, they are detected in waterways at concentrations that are lethally and sublethally toxic to aquatic organisms. Highly lipophilic, pyrethroids accumulate in sediments and bioaccumulate in fishes. Additionally, these compounds are demonstrated to act as endocrine disrupting compounds (or EDCs) in mammals and fishes, and therefore interfere with endocrine signaling by blocking, mimicking, or syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 210 publications
(107 citation statements)
references
References 167 publications
(453 reference statements)
3
101
1
2
Order By: Relevance
“…Although bifenthrin is not acutely toxic to humans and other mammals, many studies have demonstrated that bifenthrin has adverse sublethal effects in fish (Brander et al 2016). Thus, juvenile fish may experience increased seasonal temperatures during bifenthrin runoff events.…”
Section: Discussionmentioning
confidence: 99%
“…Although bifenthrin is not acutely toxic to humans and other mammals, many studies have demonstrated that bifenthrin has adverse sublethal effects in fish (Brander et al 2016). Thus, juvenile fish may experience increased seasonal temperatures during bifenthrin runoff events.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for information on population effects of EDC exposure to inform ecological risk assessments has led to the extrapolation of individual-based experimental bioassays (e.g. Jobling et al, 2002b;Miller & Ankley, 2004;Gutjahr-Gobell et al, 2006;Lange et al, 2008;Brander et al, 2016). Such extrapolations assume, however, that the effects of EDC exposure within individual-based bioassays generally show simple, direct and invariant relationships with impacts on populations and communities, even if safety factors are used to account for uncertainties associated with these extrapolations.…”
Section: The Benefits Of Up-scaling Edc Researchmentioning
confidence: 99%
“…The intensive use of pesticides causes long-term environmental contamination, resulting in human exposure. Pregnant women are particularly vulnerable to pesticide exposure because many of these human-made agricultural chemicals in use today (Brander et al, 2016;Monteagudo et al, 2016;Ventura et al, 2016) are endocrine disruptors with potentially adverse effects on embryonic and fetal development, and offspring health outcomes (Rauh et al, 2012;Dewan et al, 2013). The toxic and teratogenicity effects of pesticides could be also explained by ROS-induced oxidative stress (Al-Gubory, 2014), Animal studies show that pesticides have adverse effects on the function of the reproductive tract and the early embryonic development and survival.…”
Section: Pesticidesmentioning
confidence: 99%